A test of the Environmental Stress Hypothesis in children with and without Developmental Coordination Disorder. (July 2018) - Li, Yao-Chuen; Kwan, Matthew Y.W.; Clark, Heather J.; Hay, John; Faught, Brent E.; Cairney, John
Abstract: Objectives: This study examined several underlying mechanisms hypothesized by the Environmental Stress Hypothesis (ESH) to explain the association between probable Developmental Coordination Disorder (pDCD) and internalizing problems. Design/Method: A cross-sectional analysis involving 1206 children aged 12–14 years (79 pDCD, 6.6% of the sample) was conducted. Children received assessments of motor coordination, physical activity, BMI, global self-worth, and internalizing problems. Path analysis was conducted to examine overall model fit and sex differences. Results: The results showed significant sex differences in the underlying pathways connecting pDCD to internalizing problems, indicating more mediating pathways through physical activity, BMI and global self-worth in girls, compared to boys. Conclusions: Overall, we were able to find support for some of the pathways identified in the ESH in school-aged children. Results also suggest that the development of interventions may need to be sex specific. Highlights: School-aged children with pDCD have higher levels of internalizing problems. Internalizing problems in children with pDCD are mediated by physical activity, BMI, and global self-worth. The underlying mechanisms of internalizing problems are different between boys and girls.